Study of the Mechanical Properties of Polypropylene Composites Reinforced with Alumina Microfibers (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The purpose of this research is to create a polypropylene composite reinforced with various weight ratios of alumina filaments, as well as to study the mechanical properties of the resulting composite utilizing and without dispersion. Alumina filaments with weight ratios ranging from 2 % to 10 % were used, with a weight increase of 0.2 weight percentage. The influence of the alumina filament weight ratio on the mechanical properties of the resultant composite, such as Shore D hardness , density, modulus of elasticity, Impact strength, and tensile strength was investigated. All mechanical characteristics improved when the weight ratio of alumina filaments was raised, according to the findings. The modulus of elasticity increased from 25.5 GPa with a reinforcement ratio of 2% to 75 GPa with an 8 percent reinforcement ratio, then decreased to 70 GPa with a 10% wt. of fibers, while the density increased from 0.9 to 1.7 g/cm3 with a weight ratio of the filaments increased from 2% to 10% by weight. The impact strength increased from 1.3 kJ/cm2 to 3. 5 kJ/cm2 when the proportion of fiber by weight was increased from 2% to 8%, but the impact strength decreased to 3 kJ/cm2 when the content of alumina microfibers was 10%.. Furthermore, the Shore hardness enhanced from 20 to 45 by increasing the weight fraction of alumina fibers from 2% to 10% by weight. Tensile strength was also improved, going from 32 MPa with 2% wt. alumina microfibers to 36.5 MPa with an 8% reinforcement phase, however it dropped to 33 MPa with a 10% reinforcement phase. For all weight ratios of alumina filaments, the dispersion approach resulted in better mechanical properties such as higher tensile strength, impact strength, Shore D hardness Young's modulus, and decreased composite density.